Analysis of Influence of Pinion Tooth Trace Modification on Tooth Surface of Curved Tooth Face Gear - Zhanrong Feng; Yong Chen; Yulong Zhao; Ning Huang; Lingfeng Gao; Guangjin Xiong (Jixie chuandong)
Combining the principle of generating tooth surface of involute tooth profile curved cylindrical gear，the arc radius of the concave tooth surface of curved tooth cylindrical gear is increased，the equation to calculate cylindrical gear surface is deduced，and curved tooth cylindrical gears with different cross-section single tooth thicknesses and axes are obtained. Using curved tooth cylindrical gears as imaginary tools to derive equation for curved tooth gear surface. The face-gears with or without tooth line modification are compared，and the inner diameter analysis is carried out. The conclusion shows that the original face gear is maintained when the design parameters remain unchanged，the tooth thickness at the inner diameter of the modified face gear and the original face gear differ by 0.113 mm，and the single tooth thickness of the face gear gradually increases from inside to outside along the tooth width. Besides，the outer diameter end surface of the modified curved tooth face-gear is not pointed. Instead it is flat，to avoid the sharpening of the outer diameter tooth tip of the modified face gear. Therefore，the modification of the pinion tooth trace can increase single tooth thickness of face gear，improve the transmission strength of face gear，and provide a theoretical basis for anti-eccentric load and meshing characteristics of curved tooth face gear generated by the subsequent tooth trace modification.